2009
DOI: 10.1177/1753465809343712
|View full text |Cite
|
Sign up to set email alerts
|

Are nicotine replacement therapy, varenicline or bupropion options for pregnant mothers to quit smoking? Effects on the respiratory system of the offspring

Abstract: Nicotine occurs in tobacco smoke. It is a habit-forming substance and is prescribed by health professionals to assist smokers to quit smoking. It is rapidly absorbed from the lungs of smokers. It crosses the placenta and accumulates in the developing fetus. Nicotine induces formation of oxygen radicals and at the same time also reduces the antioxidant capacity of the lungs. Nicotine and the oxidants cause point mutations in the DNA molecule thereby changing the program that controls lung growth and maintenance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 133 publications
1
13
0
1
Order By: Relevance
“…Tobacco smoke has been previously shown to reduce the antioxidant capacity of tissues [86]. Here, we showed that like MS smoke, long-term exposure to EC aerosol significantly increases cellular ROS and decreases total cellular antioxidant capacity.…”
Section: Discussionmentioning
confidence: 51%
“…Tobacco smoke has been previously shown to reduce the antioxidant capacity of tissues [86]. Here, we showed that like MS smoke, long-term exposure to EC aerosol significantly increases cellular ROS and decreases total cellular antioxidant capacity.…”
Section: Discussionmentioning
confidence: 51%
“…In experimental studies, nicotine was capable of crossing the placenta as well as achieving concentrations in breast milk 2–3 times higher than in plasma [150]. In animal models, it has been associated with fetal central nervous system abnormalities, cardiac malformations, pulmonary hypoplasia, uteroplacental insufficiency, and sudden infant death syndrome [150,151]. In humans, it has been linked to negative birth outcomes as well.…”
Section: Tobacco Control Among Pregnant Women In the General Populmentioning
confidence: 99%
“…Although tobacco smoke contains thousands of biologically active compounds, nicotine itself is a major contributor to neurodevelopmental and autonomic abnormalities [33,34]. Accordingly, there are serious concerns as to whether the use of nicotine replacement products to achieve smoking cessation in pregnant women actually lessens perinatal risk or the subsequent appearance of neurodevelopmental deficits [4,5,20,26,34]. …”
Section: Introductionmentioning
confidence: 99%